Pelatihan Pembuatan Alat Permainan Edukatif untuk Meningkatkan Kreativitas Guru PAUD - Nurdin Salama; Hikrawati Hikrawati; Harisa Harisa (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Educational Game Tools (APE) is a basic need for teachers in providing stimulation for children. This activity aims to overcome the problem of teachers who lack knowledge and skills in making educational game tools (APE) so that it is hoped that after this activity teachers will gain knowledge and skills in making APE in addition to the variety of APE in PAUD units will support the growth and development of students . This activity uses several methods, namely lectures, demonstration discussions, exercises/practices, mentoring, and question and answer. The material in this activity is making aprons, finger puppets using flannel. The results of this activity consist of: (1) increasing the knowledge and skills of teachers in making APE media; (2) the products produced are scientific aprons, finger puppets; (3) publication in mass media; and videos. Based on the observations, it is very necessary for teachers to have skills in making various APE media that are innovative, challenging and fun without requiring large costs. Using educational game tools will overcome children who are bored in carrying out activities in class.